(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This article analyzes the development processes of theater and cinema in Uzbekistan in the years after independence. The article covers the period from 1991 to 2022, highlighting important strategies, reforms and changes for the sector. In particular, the state’s financial and creative support policies for the cinema and theater sector, international cooperation, measures taken during the pandemic, and programs aimed at education and professional development are discussed. The article also assesses the goals set for the development of the sector domestically and internationally and the processes of their implementation